BAT AGN spectroscopic survey - XV: the high frequency radio cores of ultra-hard X-ray selected AGN. Issue 3 (3rd January 2020) - Smith, Krista Lynne; Mushotzky, Richard F; Koss, Michael; Trakhtenbrot, Benny; Ricci, Claudio; Wong, O Ivy; Bauer, Franz E; Ricci, Federica; Vogel, Stuart; Stern, Daniel; Powell, Meredith C; Urry, C Meg; et al.
ABSTRACT: We have conducted 22 GHz radio imaging at 1 arcsec resolution of 100 low-redshift AGN selected at 14–195 keV by the Swift-BAT. We find a radio core detection fraction of 96 per cent, much higher than lower frequency radio surveys. Of the 96 radio-detected AGN, 55 have compact morphologies, 30 have morphologies consistent with nuclear star formation, and 11 have sub-kpc to kpc-scale jets. We find that the total radio power does not distinguish between nuclear star formation and jets as the origin of the radio emission. For 87 objects, we use optical spectroscopy to test whether AGN physical parameters are distinct between radio morphological types. We find that X-ray luminosities tend to be higher if the 22 GHz morphology is jet-like, but find no significant difference in other physical parameters. We find that the relationship between the X-ray and core radio luminosities is consistent with the LR /LX ∼ 10 −5 of coronally active stars. We further find that the canonical fundamental planes of black hole activity systematically overpredict our radio luminosities, particularly for objects with star formation morphologies.